Inactivating mutations in MFSD2A, required for omega-3 fatty acid transport in brain, cause a lethal microcephaly syndrome - Guemez-Gamboa, Alicia; Nguyen, Long N; Yang, Hongbo; Zaki, Maha S; Kara, Majdi; Ben-Omran, Tawfeg; Akizu, Naiara; Rosti, Rasim Ozgur; Rosti, Basak; Scott, Eric; Schroth, Jana; Copeland, Brett; et al. (Nature genetics, 2015)
Joseph Gleeson, David Silver and colleagues show that inactivating mutations in MFSD2A , which encodes an essential transporter of long-chain fatty acids in brain, cause a lethal microcephaly syndrome. These results establish a link between the activity of this transporter and human brain growth. Docosahexanoic acid (DHA) is the most abundant omega-3 fatty acid in brain, and, although it is considered essential, deficiency has not been linked to disease 1 , 2 . Despite the large mass of DHA in phospholipids, the brain does not synthesize it. DHA is imported across the blood-brain barrier (BBB) through the major facilitator superfamily domain–containing 2a (MFSD2A) protein 3 . MFSD2A transports DHA as well as other fatty acids in the form of lysophosphatidylcholine (LPC). We identify two families displaying MFSD2A mutations in conserved residues. Affected individuals exhibited a lethal microcephaly syndrome linked to inadequate uptake of LPC lipids. The MFSD2A mutations impaired transport activity in a cell-based assay. Moreover, when expressed in mfsd2aa -morphant zebrafish, mutants failed to rescue microcephaly, BBB breakdown and lethality. Our results establish a link between transport of DHA and LPCs by MFSD2A and human brain growth and function, presenting the first evidence of monogenic disease related to transport of DHA in humans.